2023
DOI: 10.3390/metabo13050664
|View full text |Cite
|
Sign up to set email alerts
|

Certain Tomato Root Exudates Induced by Pseudomonas stutzeri NRCB010 Enhance Its Rhizosphere Colonization Capability

Abstract: Plant growth-promoting rhizobacteria (PGPR) can colonize plant root surfaces or form biofilms to promote plant growth and enhance plant resistance to harsh external environments. However, plant–PGPR interactions, especially chemical signaling molecules, are poorly understood. This study aimed to gain an in-depth understanding of the rhizosphere interaction mechanisms between PGPR and tomato plants. This study found that inoculation with a certain concentration of Pseudomonas stutzeri significantly promoted tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Plants secrete high or low molecular weight organic compounds as root exudates in the soil that attract the selective bacteria and colonize ( Walker et al., 2003 ). A Study has shown that Pseudomonas stutzeri NRCB010 induces certain exudates from the roots of Tomato, which enhances the microbe’s colonization in the rhizosphere ( Zhang et al., 2023 ). The microbe in the bulk soil around the roots acts as an inoculum and directs microbes to colonize the rhizosphere and roots ( Bulgarelli et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plants secrete high or low molecular weight organic compounds as root exudates in the soil that attract the selective bacteria and colonize ( Walker et al., 2003 ). A Study has shown that Pseudomonas stutzeri NRCB010 induces certain exudates from the roots of Tomato, which enhances the microbe’s colonization in the rhizosphere ( Zhang et al., 2023 ). The microbe in the bulk soil around the roots acts as an inoculum and directs microbes to colonize the rhizosphere and roots ( Bulgarelli et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%